A study on the information needs and information-seeking behavior of pregnant women in Barangay UP Campus, Quezon City - Bartolome, Femush Gwynn T.; Santos, Yhna Therese, P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2019)
Pregnant women are vulnerable to various health and environmental risks which is why these women should be provided with quality health and services that would enable a safe pregnancy and delivery for them and for their child. According to Aaronson, Mural, and Pfoutz (1988), pregnancy causes physical, emotional, and social changes to a woman which may induce the need for new information to properly adjust to these new circumstances. In connection to this, information services should also be provided to pregnant women to empower them in making the right choices regarding their maternal health.

To provide the appropriate maternal information, there should be studies about what pregnant women want to know about maternal health and what sources they use in acquiring these information. While studies regarding information needs and information-seeking behavior of pregnant women are available in other countries, as of writing, there are no known studies regarding this topic in the Philippine setting. To bridge the lack of literature regarding the information needs and information-seeking behavior of Filipino pregnant women, a small-scale, barangay-level study was conducted.

For this study, 22 pregnant women who visited the Barangay UP Campus Health Station participated in either an interview or a focus group discussion to fulfill the objectives of this study. After analyzing and exploring similar themes from their answer, the information needs and information-seeking behavior of pregnant women from Barangay UP Campus, Quezon City was presented. Their evaluation methods in confirming the validity or accuracy of after acquiring the information they gathered were also determined.
Thesis
Keywords: Pregnant women -- Information needs -- Philippines -- Quezon City; Health information seeking behavior -- Philippines -- Quezon City; Information seeking behavior -- Philippines -- Quezon City